Graduate Marketing Strategy at As-Sunnah Islamic College in Deli Serdang - Maulidya, Anisa; Rafida, Tien; Fadhli, Muhammad (Tadrib: Jurnal Pendidikan Agama Islam, 2024)
This study aims to analyse the implementation of graduate marketing strategies at the As-Sunnah Islamic Religious College (STAI) Deli Serdang, using descriptive qualitative methods with data collection techniques through interviews, observations, and documentation studies. The results showed that STAI As-Sunnah implemented an inclusive marketing strategy with a direct approach through social media and digital platforms, as well as an indirect approach through alumni networks, service programmes, and social programmes. STAI As-Sunnah graduates have high competitiveness, especially in syar'i science, Arabic language, and memorisation of the Koran, and are supported by strong Islamic values. STAI As-Sunnah's graduate marketing strategy includes recruitment and job placement, adjustments to the college curriculum, partnerships with related institutions, promotion through social media, and support from alumni and universities.